Small Effect Size Pada Hubungan Adiksi Internet dengan Prestasi Akademik: Meta analisis - Amanda Meuthia Ramadhanty (Mahesa Research Center, 2022)
Internet addiction has a significant impact on people's lives, including academic achievement among students. This meta-analysis research aims to determine how much of an effect size correlation has on the relationship between internet addiction and academic achievement. This meta-analysis study used 21 literature studies with quantitative methods that ranged from 2011 to 2021, with a total of 9,981 sample. This meta-analysis uses jamovi as statistical tool. Based on the results of the meta-analysis study, it was known that internet addiction had a negative small effect size correlation on academic achievement (r =-0.19, 95% CI =-0.39 to 0.02). The 21 literature analyzed had a high level of inconsistency of 99%, and no publication bias was found in the study. Based on this, it can be known that internet addiction is not the most influential factor in individual academic achievement.